THE EFFECT OF HUMAN RESOURCE QUALITY, WORK PROFESSIONALISM, COMPENSATION AND WORK ENVIRONMENT ON ORGANIZATIONAL COMPETITIVENESS AT PT. HEXALAB SUMATERA UTARA-MEDAN - Alicia Dyna Salsabila; Winda Ardiani (CV. Radja Publika, 2026)
This study aims to determine the effect of human resource quality, work professionalism, compensation and work environment on organizational competitiveness. This study uses an associative approach with quantitative research methods, as a research analysis tool using SPSS version 25. The population in this study were all employees of PT. Hexalab North Sumatra-Medan totaling 55 people. The sampling method in this study was using the nonprobability sampling method with census sampling techniques. So the number of samples in this study was 55 employees/respondents of PT. Hexalab North Sumatra-Medan. The results of the study explain that the quality of human resources partially has a significant effect on organizational competitiveness, work professionalism partially has a significant effect on organizational competitiveness, compensation partially has no significant effect on organizational competitiveness, the work environment partially has a significant effect on organizational competitiveness and the quality of human resources, work professionalism, compensation, work environment simultaneously have a significant effect on organizational competitiveness at PT. Hexalab North Sumatra-Medan.